(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2024)
The aim of this audit was to assess the trend of the gynecological cancers for the year of 2022. This is an observational study on retrospectively collected data of gynecological cancer patients at National Institute of Cancer Research and Hospital (NICRH), Dhaka. All cases of cancer seen at the gynecology outpatient department and cases admitted in the gynecological oncology ward at NICRH, between the months of January to December 2022 were audited. The results shown that about 5.8% of all the new cases were young women aged below 25 years. The majority of gynecological cancers were among women aged between 35 and 64 years (73.17%) and only 2.6% patients were aged above 75 years. Cervical cancer (59%) was the leading gynecological cancer among all female cancers attended at NICRH. In ovarian malignancy, most of the patients(61%) had stage lll disease and no patient in stage IV diseases. Due to improper evaluation of abnormal uterine bleeding, majority of the endometrial carcinoma patients (64%) presented with histopathology reports after hysterectomy. This study might help to get a in depth understanding of the trend of major gynecological cancers. J Bangladesh Coll Phys Surg 2024; 42: 43-48